Work-Family Enrichment: Influence of Job Autonomy on Job Satisfaction of Knowledge Employees - Jing, Song; Li, Zhuoyu; Stanley, Daniel M. J. J.; Guo, Xia; Wenjing, Wang (Frontiers in Psychology, 2021)
In order to explore the specific path of the influence of job autonomy on the satisfaction of knowledge employees, the current study deduced and established a Chain Mediation Model, which was based on the Resource-Gain-Development Model and the Conservation of Resources Theory. Primary data were gathered through questionnaire surveys at several cities in China by using a professional platform named “Wenjuanxing.” The target populations were employees with a bachelor’s degree or above, who were engaged in higher knowledge content and have mastered certain professional knowledge and skills, including technical R & D personnel, management personnel, professionals (such as accountants, lawyers, and medics) and other personnel generally recognized by the academic community. In order to improve the reliability of the sample and reduce the error caused by regional differences, the questionnaires were disseminated to involve as many cities in China as possible, such as Tianjin, Beijing, Chengdu, Wuhan, and Guangzhou. SPSS24.0 and Aoms24.0 were used as multivariate data analysis tools for statistical analysis. The results showed that job autonomy can significantly improve the satisfaction of knowledge employees; however, it cannot affect the satisfaction of knowledge employees through self-efficacy. The findings of the study also revealed that job autonomy has a positive impact on both resource source domain satisfaction and resource acceptance domain satisfaction through work-family enrichment, especially the positive emotions in the resource source domain. Job autonomy improves the self-efficacy of knowledge employees, which, in turn, improves their overall satisfaction through the work-family enrichment path.